Optimal CD8+ T‐cell memory formation following subcutaneous cytomegalovirus infection requires virus replication but not early dendritic cell responses. Issue 2 (13th June 2021) - Dimonte, Sandra; Gimeno‐Brias, Silvia; Marsden, Morgan; Chapman, Lucy; Sabberwal, Pragati; Clement, Mathew; Humphreys, Ian R
Summary: Cytomegalovirus (CMV) induction of large frequencies of highly functional memory T cells has attracted much interest in the utility of CMV‐based vaccine vectors, with exciting preclinical data obtained in models of infectious diseases and cancer. However, pathogenesis of human CMV (HCMV) remains a concern. Attenuated CMV‐based vectors, such as replication‐ or spread‐deficient viruses, potentially offer an alternative to fully replicating vectors. However, it is not well understood how CMV attenuation impacts vector immunogenicity, particularly when administered via relevant routes of immunization such as the skin. Herein, we used the murine cytomegalovirus (MCMV) model to investigate the impact of vector attenuation on T‐cell memory formation following subcutaneous administration. We found that the spread‐deficient virus (ΔgL‐MCMV) was impaired in its ability to induce memory CD8 + T cells reactive to some (M38, IE1) but not all (IE3) viral antigens. Impaired‐memory T‐cell development was associated with a preferential and pronounced loss of polyfunctional (IFN‐γ + TNF‐α + ) T cells and also reduced accumulation of TCF1 + T cells, and was not rescued by increasing the dose of replication‐defective MCMV. Finally, whilst vector attenuation reduced dendritic cell (DC) recruitment to skin‐draining lymph nodes, systematic depletion of multiple DC subsets during acute subcutaneous MCMV infection had a negligible impact on T‐cell memory formation, implying that attenuated responses induced by replication‐deficient vectors were likely not a consequence of impaired initial DC activation. Thus, overall, these data imply that the choice of antigen and/or cloning strategy of exogenous antigen in combination with the route of immunization may influence the ability of attenuated CMV vectors to induce robust functional T‐cell memory. Abstract : Cytomegalovirus (CMV) is a potentially exciting vaccine vector, but pathogenicity may preclude the use of replicating viruses. Here, we show that a spread‐deficient CMV vector is attenuated in the ability to induce T‐cell memory formation after subcutaneous immunization. This results in pronounced loss of polyfunctional T cells, possibly linked to reduced development of TCF1‐expressing T cells.